2020
DOI: 10.1002/jgf2.302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shakuyaku‐kanzo‐to in patients with muscle cramps: A systematic literature review

Abstract: Background Previous clinical studies have reported that Shakuyaku‐kanzo‐to (SKT) has a therapeutic effect on muscle cramps, but few studies have clarified how SKT acts to treat muscle cramps. The aim of this study was to perform an updated systematic review of clinical trials for SKT in patients with muscle cramps. Methods The literature was systematically reviewed to assess the effects of SKT in patients with muscle cramps. PubMed, Web of Science, Cochrane Library, Google Scholar, and Ichushi‐Web were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…In clinical practice, this remedy is commonly employed in treating muscle cramps as well as crampy pain. 28 Some recent studies using both animal models and human patients observed that SYGCT was beneficial in attenuating the plasma levels of pro-inflammatory cytokines by modulating the activation of NF-κB signaling pathway. 29 , 30 Not only being a key marker of inflammatory response, NF-κB is often considered one of the most critical muscle transcription factors, since its activation provokes muscle loss and muscular dystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, this remedy is commonly employed in treating muscle cramps as well as crampy pain. 28 Some recent studies using both animal models and human patients observed that SYGCT was beneficial in attenuating the plasma levels of pro-inflammatory cytokines by modulating the activation of NF-κB signaling pathway. 29 , 30 Not only being a key marker of inflammatory response, NF-κB is often considered one of the most critical muscle transcription factors, since its activation provokes muscle loss and muscular dystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Jia-Wei-Xiao-Yao-San has been demonstrated that it can adjust the abnormal gastric motility and gastric myoelectrical activity of patients with functional dyspepsia ( Qu et al, 2010 ). Shao Yao Gan Cao Tang, a frequently prescribed harmonizing formula in CKD, is efficacy in relieving muscle pain or skeletal muscle tremors in patients undergoing hemodialysis or with cirrhosis or lumbar spinal stenosis ( Hinoshita et al, 2003 ; Ota et al, 2020 ). Our findings suggest symptoms involving the digestive system composite the main syndromes for typical harmonizing formulas prescription ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the potassium level had increased to 5.8 mEq/L at the end of treatment in only one patient. As mentioned in an earlier systematic review of muscle cramps by Ota et al [45], they also suggest that patients be monitored for pseudoaldosteronism during long-term use of SYGCT.…”
Section: Muscle Crampsmentioning
confidence: 93%